Melanotic neuroectodermal tumour of infancy: report of a case - Singh, A; Khanna, S D; Kanta, S (Australian and New Zealand journal of surgery, 1976)
A case of melanotic neuroectodermal tumour occurring in a seven-month-old male infant is reported. The aetiopathogenesis, clinical features, treatment and prognosis of the condition are discussed. Tumours of the jaw in infancy are extremely rare, and pigmented tumours still rarer. One such case of pigmented tumour of the maxilla is the subject of this report.